Relations between nursing data collection, diagnoses and prescriptions for adult patients at an intensive care unit (Revista Latino-Americana de Enfermagem, 2008)
This descriptive, retrospective study aimed to analyze the relation between nursing data collection, diagnoses and prescriptions for 26 adult patients who were hospitalized at the intense care unit of a large teaching hospital for at least 24 hours. Through the analysis of medical records, 135 diagnoses and 421 nursing prescriptions were established, and 24 different diagnosis categories and 20 different items for prescriptions were identified. The most frequent diagnosis risk was that for infection, present in the medical records of 22 (84.60%) patients, with 175 prescriptions (42%) related to this diagnosis. The data the nurses collected were sufficient to establish the nursing diagnoses, and the majority of prescriptions (87.9%) were related to the diagnoses.